2019
DOI: 10.3168/jds.2018-15033
|View full text |Cite
|
Sign up to set email alerts
|

A new method of administering local anesthesia for calf disbudding: Findings from a comparative on-farm study in New Zealand

Abstract: Anesthesia of the horn bud for calf disbudding commonly is attained by injection of local anesthetic over branches of the cornual nerve, with anesthesia achieved in 3 to 20 min. With experienced and trained staff, this method is effective in 88 to 100% of calves. Variability in response and time of onset can compromise calf welfare if calves are disbudded before anesthesia is attained. Proposed legislative reliance on effective local anesthetic as the minimal method of pain relief for calves at disbudding mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…A reduction in play has been observed 3 h after a lidocaine cornual nerve block in sham-disbudded calves, which may indicate continued discomfort at the injection sites after the anesthesia has worn off (Mintline et al, 2013). However, Bates et al (2019) found no differences in head shaking, head scratching, or head rubbing in the 3 h after lidocaine injection in sham-disbudded calves compared with non-injected controls. Further research is warranted on the physiological and affective consequences of lidocaine.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A reduction in play has been observed 3 h after a lidocaine cornual nerve block in sham-disbudded calves, which may indicate continued discomfort at the injection sites after the anesthesia has worn off (Mintline et al, 2013). However, Bates et al (2019) found no differences in head shaking, head scratching, or head rubbing in the 3 h after lidocaine injection in sham-disbudded calves compared with non-injected controls. Further research is warranted on the physiological and affective consequences of lidocaine.…”
Section: Discussionmentioning
confidence: 82%
“…In accordance with this theory, calves reduced rubbing their head on objects or pushing it against penmates, in the first 4 h after hot-iron disbudding without local anesthesia (Morisse et al, 1995;Graf and Senn, 1999). However, despite these early findings, subsequent studies observed either no change in time spent rubbing or touching the head against objects or penmates after hot-iron disbudding (Doherty et al, 2007;Mintline et al, 2013;Bates et al, 2019), or have reported more head rubbing in calves disbudded with a hot-iron (Faulkner and Weary, 2000;Heinrich et al, 2010;Stilwell et al, 2012;Huber et al, 2013) or caustic paste (Vickers et al, 2005;Stilwell et al, 2009) compared with non-disbudded calves. Interestingly, however, all the studies that reported more head rubbing defined the behavior entirely or in part as scratching with the hindfeet.…”
Section: Discussionmentioning
confidence: 85%
“…A number of studies have focused on the acute pain response to cautery disbudding [ 33 36 ] and of the benefits of providing local anaesthesia and pain relief [ 12 , 37 41 ] at the time of disbudding. Adcock and Tucker [ 36 ] reported that calves disbudded at 3 d versus 35 d of age were more sensitive to pain after disbudding.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have focused on the acute pain response to cautery disbudding [33][34][35][36] and of the Table 2 Effect of sex, age and year on horn bud diameter (mm) and height (mm) of suckler-bred male and female calves at disbudding (n = 191) benefits of providing local anaesthesia and pain relief [12,[37][38][39][40][41] at the time of disbudding. Adcock and Tucker [36] reported that calves disbudded at 3 d versus 35 d of age were more sensitive to pain after disbudding.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological agents used in the management of pain include opioids, nonsteroidal anti-inflammatory drugs, steroidal anti-inflammatory drugs, and local anesthetics [25]. Additionally, tranquilizers, corticosteroids, tricyclic antidepressants and antiepileptic medications (topical capsaicin, mexiletine, and N-methyl-d-aspartate receptor antagonists), serotonin norepinephrine reuptake inhibitors, calcium channel α2-δ ligands, topicals, anticonvulsants, and transdermal substances are included in the pain management regimen as adjuvants to analgesics depending on the type and severity of pain [26][27][28][29]. Nonpharmacological management of pain involves the use of suitable housing, bed rest, gentle handling and manipulation (massage, osteopathic and chiropractic), meditative movements (such as Tai Chi and yoga), and diets [30,31].…”
Section: Pain Managementmentioning
confidence: 99%